Penerapan POJK 44/2020 dalam Manajemen Risiko Asuransi Syariah Al Amin - Hanifah Syifa Maulida; Indra Marzuki (JURNAL ILMIAH NUSANTARA, 2026)
This research aims to analyze Risk Management Practices at PT Asuransi Jiwa Syariah Al Amin and assess its compliance with POJK Number 44/POJK.05/2020 regarding the implementation of risk management for non-bank financial service institutions. The type of research used is qualitative in the form of a case study with a juridical-empirical law approach. The research results show that, first, PT Asuransi Jiwa Syariah Al Amin has implemented risk management through the Three Lines of Defense framework and the Risk Control Self Assessment (RCSA) method which includes identification, measurement, control, and risk monitoring. Second, the practice is generally in accordance with the provisions of POJK Number 44/POJK.05/2020 regarding the implementation of risk management for non-bank financial service institutions, especially in the management of nine types of risks and reporting to supervisory agencies. However, the obligation to have an integrated risk management information system has not been fully fulfilled because data management is still manual.